Effects of Bisphenol A on Haematological, Gonadal Gene Expression and Histopathological Biomarkers in Genetically Improved Farmed Tilapia - Shyam Lal Tudu; Sriram, P Sriram; Uma Arumugam; Nallaiah Hemamalini; S.A. Shanmugam (The Indian Veterinary Journal, 2026)
Bisphenol A (BPA), a common aquatic contaminant, was tested on Genetically Improved Farmed Tilapia (GIFT) juveniles. The 96‑h median lethal concentration was 6.794 mg/L. Sublethal exposure (4–6 mg/L for 7 days) altered haematology, histopathology, and gonadal defense gene expression. Leukocyte counts rose significantly at 4 mg/L, while erythrocyte counts decreased across treatments. MCV, MCH, and MCHC values increased. Histopathological damage was evident in gills, gonads, brain, and kidney. Defense genes GST, OP450, and p53 were upregulated in gonads. Overall, BPA exposure significantly disrupted blood parameters, tissue integrity, and cellular defense mechanisms in GIFT juveniles.